Pengaruh Bi’ah Lughowiyyah terhadap Maharah Kalām dalam Pembelajaran Bahasa Arab - Said, Azizah Saad; Noor Fadjri, Muhammad Fikri (Mahira: Journal of Arabic Studies & Teaching, 2025)
The limited of speaking skill among learners of Arabic remains a common issue in many Islamic educational institutions. Although Arabic is formally taught, many students are still unable to use it effectively as a means of communication. This study employed a quantitative descriptive approach to investigate the influence of bi’ah lughawiyyah on maharah kalām among 136 students of MTs Muallimin Muhammadiyah Yogyakarta. A Likert-scale questionnaire was used as the research instrument, developed based on theoretical indicators of language acquisition and speaking skills. Data were analyzed using normality tests, linearity tests, and simple linear regression through SPSS. The findings revealed that students’ bi’ah lughawiyyah was in the high category, while their maharah kalām ranged from moderately good to high. Regression analysis indicated a significant influence between the two variables Sig. 0.000 < 0.05 with a contribution of 13.7%. These results indicate that a stronger language environment corresponds to higher speaking ability, although other factors also play a role. In conclusion, bi’ah lughawiyyah contributes significantly to the improvement of maharah kalām, but it is not the sole determinant of speaking competence.